2018
DOI: 10.17508/cjfst.2018.10.1.07
|View full text |Cite
|
Sign up to set email alerts
|

Properties influencing cracking and separation of palm nuts in a mechanical cracker cum separator

Abstract: Experimental studies of some properties influencing cracking and separation of palm kernel from the shell was conducted in a palm kernel dual processing machine. A mechanical cracking cum separating machine was developed for the study. The cracking unit consists of feed hopper, impeller shaft, cracking drum and impeller blade. The nut falls by gravity through the hopper channel into the cracking drum where the cracking process takes place through the help of impeller blades that flip the palm nut against the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…to highest value of 97% at 8.92% moisture content (db.). The decrease might be due to the fact that the palm nut become more brittle and susceptible to cracking at low moisture content (Olaoye and Adekanye,., 2018). Kilanko et al (2018) reported that the shell of the nut is naturally spongy and tough at lower moisture content.…”
Section: Quality Performance Efficiencymentioning
confidence: 99%
“…to highest value of 97% at 8.92% moisture content (db.). The decrease might be due to the fact that the palm nut become more brittle and susceptible to cracking at low moisture content (Olaoye and Adekanye,., 2018). Kilanko et al (2018) reported that the shell of the nut is naturally spongy and tough at lower moisture content.…”
Section: Quality Performance Efficiencymentioning
confidence: 99%
“…The allowed bending stress (γ d ), and safety factor (SF) for the shaft with keyways were 40 Nm.m -2 and 1.5 respectively (Hassan et al, 2009). The shaft diameter was calculated to be 24 mm from Equation 16 (Olaoye and Adekanye, 2018). The standard available shaft size of 25 mm diameter was selected for this study based on the power calculations above.…”
Section: Shaft Sizingmentioning
confidence: 99%
“…The machine performance was evaluated by measuring the weight of groundnuts shelled per unit time. Equation 29 was used to calculate the machine capacity (Olaoye and Adekanye, 2018).…”
Section: Sheller Performance Evaluationsmentioning
confidence: 99%
“…% MC= (W2-W3 (moisture loss))/(W2-W1(fresh weight)) ×100 The same procedure was used by [25] in their recent research work on the properties affecting the cracking of palm nut.…”
Section: Determination Of Moisture Contentmentioning
confidence: 99%